Parallel Allostery by cAMP and PDE Coordinates Activation and Termination Phases in cAMP Signaling - Krishnamurthy, Srinath (Biophys J, 2015)
The second messenger molecule cAMP regulates the activation phase of the cAMP signaling pathway through high-affinity interactions with the cytosolic cAMP receptor, the protein kinase A regulatory subunit (PKAR). Phosphodiesterases (PDEs) are enzymes responsible for catalyzing hydrolysis of cAMP to 5′ AMP. It was recently shown that PDEs interact with PKAR to initiate the termination phase of the cAMP signaling pathway. While the steps in the activation phase are well understood, steps in the termination pathway are unknown. Specifically, the binding and allosteric networks that regulate the dynamic interplay between PKAR, PDE, and cAMP are unclear. In this study, PKAR and PDE from Dictyostelium discoideum (R(D) and RegA, respectively) were used as a model system to monitor complex formation in the presence and absence of cAMP. Amide hydrogen/deuterium exchange mass spectrometry was used to monitor slow conformational transitions in R(D), using disordered regions as conformational probes. Our results reveal that R(D) regulates its interactions with cAMP and RegA at distinct loci by undergoing slow conformational transitions between two metastable states. In the presence of cAMP, R(D) and RegA form a stable ternary complex, while in the absence of cAMP they maintain transient interactions. RegA and cAMP each bind at orthogonal sites on R(D) with resultant contrasting effects on its dynamics through parallel allosteric relays at multiple important loci. R(D) thus serves as an integrative node in cAMP termination by coordinating multiple allosteric relays and governing the output signal response.